Identification of the RNA-Binding, Dimerization, and eIF4GI-Binding Domains of Rotavirus Nonstructural Protein NSP3 - Piron, Maria (American Society for Microbiology, 1999)
The rotavirus nonstructural protein NSP3 is a sequence-specific RNA binding protein that binds the nonpolyadenylated 3′ end of the rotavirus mRNAs. NSP3 also interacts with the translation initiation factor eIF4GI and competes with the poly(A) binding protein. Deletion mutations and point mutations of NSP3 from group A rotavirus (NSP3A), expressed in Escherichia coli, indicate that the RNA binding domain lies between amino acids 4 and 149. Similar results were obtained with NSP3 from group C rotaviruses. Data also indicate that a dimer of NSP3A binds one molecule of RNA and that dimerization is necessary for strong RNA binding. The dimerization domain of NSP3 was mapped between amino acids 150 and 206 by using the yeast two-hybrid system. The eukaryotic initiation factor 4 GI subunit (eIF-4GI) binding domain of NSP3A has been mapped in the last 107 amino acids of its C terminus by using a pulldown assay and the yeast two-hybrid system. NSP3 is composed of two functional domains separated by a dimerization domain.